Musculoskeletal injuries in physical education versus non-physical education teachers: a prospective study. Issue 12 (17th June 2016) - Goossens, Lennert; Vercruysse, Sien; Cardon, Greet; Haerens, Leen; Witvrouw, Erik; De Clercq, Dirk
ABSTRACT: Physical education (PE) teachers have a physically demanding job, putting them at a considerable risk for musculoskeletal injuries. To structurally develop tailored injury prevention programmes for PE teachers, a clear understanding of the extent, characteristics and underlying factors of their musculoskeletal injuries compared to referents is necessary. Therefore, the current study prospectively followed 103 PE teachers and 58 non-PE teachers, who registered musculoskeletal injuries and time of exposure to sports participation during one school year. Pearson χ 2 -tests and independent samples t -tests determined significant differences between PE and non-PE teachers regarding demographics and variables possibly related to injury occurrence. PE teachers had 1.23 and non-PE teachers 0.78 injuries/teacher/school year. This difference was significantly different after adjustment for hours spent weekly on intracurricular teaching during the career and for injury history during the preceding six months ( P = 0.009; OR = 0.511; 95% CI = 0.308–0.846). PE teachers' most affected body parts were the knee and the back. PE teachers had a more extensive injury history ( P < 0.001), a higher work- ( P < 0.001) and sport index ( P < 0.001), practiced more sports ( P < 0.002) and taught more extracurricular sports ( P = 0.001). Future injury prevention programmes should take account for the great injury history and heavy physical load in PE teachers.